Identification and Mapping of the Replication Genes of an R Factor, R100-1, Integrated into the Chromosome of Escherichia coli K-12 - Yoshikawa, Masanosuke (1974)
A stable Hfr strain of Escherichia coli K-12 was obtained by integrative suppression by an R factor, R100-1. The R factor was integrated into the right of 81 min, and chromosome transfer occurred counterclockwise. Mating experiments revealed two linkage groups of genes on the R factor. Drug-resistant transductants of a dnaA-ts recipient from an R-factor Hfr and from an R(+) strain differ in their drug resistance patterns, temperature sensitivity, and transferability of drug resistance as well as chromosome markers. Transductants that transferred chromosome markers were further classified as to the origin and direction of chromosome transfer. For temperature-sensitive transductants, the reversion frequency to temperature resistance was determined, and these revertants were scored for transfer of drug resistance as well as chromosome markers. Two genes responsible for integrative suppression (designated as repA) and the other for autonomous replication (designated as repB) were identified and mapped. The arrangement of genes on the R factor is... (sul, str, cml)... repA... tra... (tet, repB).... The map of the autonomously replicating R factor is probably a circle connecting both sides of this linear map. Thus, a method has been established to map a plasmid that could not finely be analyzed under autonomous state by transduction. It also permits genetic analysis of genes responsible for replication of the plasmid without making use of a conditional mutant of itself but with that of the host, dnaA.